The resurgence of sovereign power in the face of the pandemic - Chavarria, Stuart Daniel (2024)
This article focuses on analyzing how the sovereign power of life and death was exercised during the COVID-19 pandemic in Costa Rica in 2020. The article tries to question the Foucauldian approach that sovereign power represents a attenuated power since it can be observed on the restrictions on mobility and the delegation of the decision on life and death in the medical power how the sovereign power continues in modern legal systems operating beyond the limits of the state of emergency.